Wild Termitomyces Species Collected from Ondo and Ekiti States Are More Related to African Species as Revealed by ITS Region of rDNA - Victor Olusegun Oyetayo (The Scientific World Journal)
Molecular identification of eighteen Termitomyces species collected from two states, Ondo and Ekiti in Nigeria was carried out using the internal transcribed spacer (ITS) region. The amplicons obtained from rDNA of Termitomyces species were compared with existing sequences in the NCBI GenBank. The results of the ITS sequence analysis discriminated between all the Termitomyces species (obtained from Ondo and Ekiti States) and Termitomyces sp. sequences obtained from NCBI GenBank. The degree of similarity of T1 to T18 to gene of Termitomyces sp. obtained from NCBI ranges between 82 and 99 percent. Termitomyces species from Garbon with ascension number AF321374 was the closest relative of T1 to T18 except T12 that has T. eurhizus and T. striatus as the closet relative. Phylogenetic tree generated with ITS sequences obtained from NCBI GenBank data revealed that T1 to T18 are more related to Termitomyces species indigenous to African countries such as Senegal, Congo, and Gabon.